Video Watermarking Technique with High Robustness and Embedding Capacity - Upadhyay, Jayprakash; Mishra, Bharat; Patel, Prabhat (International Journal of Computer Sciences and Engineering, 2025)
This work investigates a technique of watermarking for secured communication. Now a day’s authorized access of multimedia data has been increasing rapidly and it demands higher security. A new modified LSB watermarking embedding technique is presents in this regards. The main objective of this technique is to provide highest robustness against different types of attacks like rotation, cropping, noise and filtering. Simulation result of proposed work has been shown to claim the better robustness.